Sejarah Trah Yudanegaran - Sugeng Priyadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2004)
The interesting free-family of yudonegara of Banyumas can be traced from various historical texts about Banyumas. It is known that Yudonegara I until Yudonegara V had ruled Banyumas. The power of Surakarta kings were so great and they had strong influence in the changes of power. The Yudonegara V free family ended after Yudonegara V was forced to leave his power by external factors. Banyumas was then split into two parts, namely Kesepuhan and Kanoman.